Looking beyond climate contrarianism: nationalism and the reterritorialization of climate discourse in Spain’s Vox party - Johanna Hanson (Nordia Geographical Publications, 2023)
Among European populist radical right (PRR) parties, the call for environmental protection has historically been embedded in ethnic nationalist ideas of the interrelation of land, nation, and culture. Despite a large body of literature on PRR environmentalism, however, the PRR’s climate politics remain understudied. This qualitative study investigates the climate politics of the PRR by analyzing climate discourse from Spain’s Vox party. A discourse analysis of party manifestos, press releases, and public statements from 2017–2022 investigates Vox’s discursive constructions of climate change and its potential solutions. The study finds that, although the party acknowledges climate change, it does so inconsistently, and its proposed climate policies do not fundamentally shift its nativist and populist political imagination. Instead, its discourse portrays multilateral climate action as a threat to the nation and locates climate solutions in the preservation of ruralism, traditional livelihoods, and national identity. The article argues that Vox constructs a nationalist climate discourse that reterritorializes climate change on the national level, asserts national innocence in the face of claims of global climate justice, and frames mainstream climate action as part of a broader globalist imposition that threatens the purity of national culture. The article concludes with reflections on what nationalist climate discourse may mean for attempts to mitigate the climate crisis.